Cortical pathology and cognitive impairment in multiple sclerosis. (March 2011) - Calabrese, Massimiliano; Rinaldi, Francesca; Grossi, Paola; Gallo, Paolo
Cognitive impairment constitutes a relevant clinical aspect of multiple sclerosis (MS). Depending on the disease phase and type, 40––65% of MS patients develop various degrees of cognitive dysfunction. Pathological and MRI studies have failed to demonstrate the existence of a strict relationship between cognitive impairment and subcortical white matter pathology. The correlation is also poor when MRI metrics of whole brain (white plus gray matter) atrophy are considered. Over the last decade, increasing observations have provided evidence of a primary role of cortical pathology –– that is, inflammatory focal lesions (cortical lesions) and atrophy (cortical thickness) –– in determining global and/or selective cognitive disability in MS. By applying a new semi-automated software (Freesurfer) to analyze the global and regional cortical thickness and the double inversion recovery sequence to identify cortical lesions, it has been observed that specific cognitive deficits, such as memory impairment, attention deficits and reduced mental processing speed, could be better explained by cortical structural abnormalities rather than subcortical white matter lesions. Therefore, MRI evaluation of cortical pathology should be included in the routine examination of MS patients, especially those with initial signs/symptoms of cognitive dysfunctions.